Shatibi’s theories of knowledge as seen in his al-Muwafaqat: a preliminary study - Fadzil, Ammar; Ahmed Ali, Ahmed El-Mogtaba Bannga; Awang Hamat, Mohd Afandi (Common Ground Publishing Pty Ltd, 2008)
This article aims to highlight Shatibi’s theory of knowledge according to his renowned work, al-Muwafaqat. Shatibi’s theory of knowledge is greatly influenced by his theory of maqasid (objectives of legal rulings). He pointed out a number of issues, namely types of knowledge, purposes of pursuing knowledge, transmission of knowledge and the role of reason vis-a-vis revelation. He also discusses the position of a learned person. In doing so, he employs a variety of legal evidence, especially the Qur’an and the hadith of the Prophet. This article argues that Shatibi’s conception of knowledge is relatively different from that of his predecessors and thus would enhance intellectual discussions on the theory of knowledge.